Functional end-arterial circulation of the choroid assessed by using fat embolism and electric circuit simulation - Ji Eun Lee (Nature Portfolio, 2017)
Abstract The discrepancy in the choroidal circulation between anatomy and function has remained unsolved for several decades. Postmortem cast studies revealed extensive anastomotic channels, but angiographic studies indicated end-arterial circulation. We carried out experimental fat embolism in cats and electric circuit simulation. Perfusion defects were observed in two categories. In the scatter perfusion defects suggesting an embolism at the terminal arterioles, fluorescein dye filled the non-perfused lobule slowly from the adjacent perfused lobule. In the segmental perfusion defects suggesting occlusion of the posterior ciliary arteries, the hypofluorescent segment became perfused by spontaneous resolution of the embolism without subsequent smaller infarction. The angiographic findings could be simulated with an electric circuit. Although electric currents flowed to the disconnected lobule, the level was very low compared with that of the connected ones. The choroid appeared to be composed of multiple sectors with no anastomosis to other sectors, but to have its own anastomotic arterioles in each sector. Blood flows through the continuous choriocapillaris bed in an end-arterial nature functionally to follow a pressure gradient due to the drainage through the collector venule.